Developing the sales potential of cartier in Portugal: which communication strategy should be implemented by cartier to attract Millennials & Gen Z - Andrade, Leonor Alves da Costa Ferreira de (2021)
The Maison Cartier is one of the most distinguished Luxury Jewellery and Watchmaking Market brands. Cartier aims to develop its sales potential towards national consumers and attract the younger generations in Portugal. The present Work Project defines a communication strategy that Cartier should implement to attract Portuguese Millennials & Gen Z. Therefore, the main objectives for this recommended communication strategy focus on strengthening the connection and relationship with consumers, on increasing communication touchpoints, on communicating the jewellery pieces and watches that can be most attractive to consumers, and finally, on shifting consumers mature perception of Cartier towards a younger one.